Colloidal silicon dioxide with rough surface as well as preparation method and application of colloidal silicon dioxide
By preparing high-purity surface rough spherical colloidal silica, the problem of insufficient cutting force of existing abrasives is solved, and the high polishing rate and high purity are achieved, which is suitable for semiconductor CMP fields.
Patent Information
- Application Number
- CN202510454516.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-11
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-04-11
AI Technical Summary
The surface smooth properties of existing semiconductor CMP abrasives lead to insufficient mechanical cutting force, which makes it difficult to meet the demand for high polishing rates. At the same time, it is difficult to maintain high purity and monodispersity in the process of increasing the polishing rates.
A high-purity surface rough spherical colloidal silica is prepared by reacting silicone with charge adjusting agent and alkaline amino acids to form a chain branched chain structure, and combined with low-temperature and reduced pressure distillation technology, surface rough silica with high purity and monodispersity is prepared.
It significantly improves the mechanical cutting force of silicon abrasive during grinding, shortens the preparation cycle, reduces overall energy consumption, meets the purity requirements of the semiconductor level, and improves polishing efficiency.
Smart Images

Figure CN119954164A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor chemical mechanical polishing (CMP), and in particular to high-purity spherical colloidal silicon dioxide with rough surface and a preparation method thereof. Background Art
[0002] Chemical mechanical polishing (CMP) is the core technology for achieving global flattening of wafers in semiconductor manufacturing. Its performance directly depends on the morphology, purity and mechanochemical synergy of the abrasive in the grinding composition. The current mainstream CMP abrasive is mainly high-purity spherical colloidal silica, which is prepared by hydrolysis and condensation of siloxane under alkaline conditions. Although this type of abrasive has the advantages of uniform morphology and good dispersibility, its smooth surface characteristics lead to insufficient mechanical cutting force, which makes it difficult to meet the requirements of advanced processes for high polishing rates.
[0003] In the prior art, attempts to increase the polishing rate are mainly concentrated in the following two types of solutions: morphology control, giving the silica abrasive a rough surface through surface etching (such as CN112142020A) or composite polymer coating (such as US2018035512A1), but the former is prone to introduce metal ion contamination, and the latter causes a decrease in purity due to organic residues (metal impurities > 5ppm), both of which are difficult to meet semiconductor-grade purity requirements; process optimization, extending the aging time (8-12 hours) to increase the particle size, although it can slightly increase the cutting force, but leads to low production efficiency and deterioration of the particle size distribution.
[0004] In addition, the traditional process requires the use of metal catalysts (such as NaOH, etc.) to control the morphology, and the residual sodium ions in the final product often reach 2-5ppm, requiring additional purification steps, further increasing the cost. Therefore, how to give silica abrasives a controllable rough surface and shorten the preparation cycle while ensuring high purity (metal / anion ≤ 1ppm) and monodispersity (PDI ≤ 0.1) has become a technical bottleneck that needs to be broken through in the semiconductor CMP field. Summary of the invention
[0005] The purpose of the present invention is to provide a high-purity spherical colloidal silica with a rough surface and a preparation method thereof, so as to improve the mechanical cutting force of silicon abrasives during the grinding process and realize the improvement of grinding efficiency.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing high-purity rough-surface spherical colloidal silica: The method for preparing high-purity monodisperse spherical colloidal silica for CMP of the present application comprises the following steps: (a) Using siloxane as a raw material, adding a charge regulator aminopropylsilane and an alcohol solvent and mixing and stirring to form a mixed solution A; (b) mixing an alcohol solvent, an alkaline amino acid, ultrapure water and an alkaline substance to prepare a mixed solution B; (c) mixing solution A and solution B to react to prepare a silica sol; (d) distilling the silica sol under reduced pressure, and adding water to replace and remove the alcohol therein, thereby obtaining a colloidal silica with a rough surface.
[0007] Furthermore, the alkaline substance includes one or more of ammonia water, tetramethylammonium hydroxide, and triethoxypropylamine, preferably ammonia water; Furthermore, the concentration of the alkaline substance in solution B is 0.1-10wt%, preferably 0.5-5wt%.
[0008] Further, the siloxane is selected from one or a combination of tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, mercaptopropyltrimethoxysilane, epoxytrimethoxysilane, and mercaptopropyltriethoxysilane; And / or, the charge regulator is selected from one or a combination of aminopropyltrimethoxysilane or aminopropyltriethoxysilane; And / or, the alcohol solvent includes one or more combinations of methanol, ethanol, isopropanol, butanol, isoamyl alcohol, ethylene glycol, and propylene glycol, preferably one or more combinations of methanol, ethanol, and isopropanol; more preferably methanol or ethanol; And / or, the basic amino acid is selected from at least one of lysine, arginine, histidine, ornithine and citrulline, preferably lysine, arginine or a combination thereof.
[0009] Further, in step (a), the content of the charge regulator is 1-10 wt % of solution A, preferably 2-5 wt %; and / or, the content of the alcohol solvent in step (a) is 1-50 wt %, preferably 20-30 wt % of solution A; and / or, the concentration of the basic amino acid in solution B is 0.1-3wt%, preferably 0.5-1wt%; And / or, the concentration of the alcohol solvent in solution B in step (b) is 60-90wt%, preferably 70-80wt%.
[0010] Furthermore, in the step (c), the mass ratio of solution A to solution B is 1:1-20, preferably 1:2-10; and / or, the reaction temperature of solution A and solution B is 30-40° C., preferably 33-37° C.; And / or, the reaction time of solution A and solution B is 1-8h, preferably 1-2h; Furthermore, the step (d) is: concentrating the silica sol by vacuum distillation, and then performing constant liquid position replacement at normal pressure. When the liquid temperature and the tower top temperature reach 100°C, the replacement is completed, and a high-purity monodisperse silica sol with a rough surface can be obtained.
[0011] Furthermore, the temperature range of the vacuum distillation is 40-80° C., and the vacuum distillation is concentrated to a solid content of 10-40wt%.
[0012] The second aspect of the present invention provides a spherical colloidal silica with a rough surface, wherein the colloidal silica is prepared by the above method.
[0013] Furthermore, the PDI of the colloidal silica is ≤0.1, the metal ion impurities are <1ppm, and the anion impurities are ≤1ppm.
[0014] The third aspect of the present invention provides a CMP polishing composition comprising the above-mentioned colloidal silica abrasive.
[0015] The fourth aspect of the present invention provides the use of the above-mentioned colloidal silica as an abrasive in CMP mechanical polishing. In the present invention, silane is hydrolyzed and condensed to form silica nanoparticles, and the charge regulator is hydrolyzed and condensed with the silica nanoparticles to connect the amino functional groups to the surface of the nanoparticles to form sites for the condensation of basic amino acids. The basic amino acids condense with the amino groups on the surface of the nanoparticles and continue to condense with the amino acids to form a chain-like branched structure to form protrusions. At the same time, the silane continues to hydrolyze, condense and grow to form nanoparticles with rough surfaces. Compared with existing high-purity CMP abrasives, the product has significant differences in morphology. In the present invention, the organic acid, inorganic base, and methanol used can be removed during the distillation process without introducing metal ion impurities. The metal ion impurities of the prepared colloidal silica are less than 1ppm, and the anion impurities are ≤1ppm. Beneficial Effects
[0016] The preparation method of the present invention has a greatly shortened reaction cycle. Compared with the traditional process, the present invention can shorten the reaction time to 1-2 hours, and achieves efficient purification through low-temperature reduced pressure distillation (40-80°C), reduces overall energy consumption, and is suitable for industrial continuous production.
[0017] The colloidal silica prepared by the method of the present invention has high purity. The present invention adopts specific amino acids, alkaline substances, and solvents, and has no metal catalyst residue. The total amount of metal ion impurities in the obtained colloidal silica is less than 1ppm, and the total amount of anion impurities is ≤1ppm, which meets the purity requirements in semiconductor mechanical polishing.
[0018] The colloidal silica prepared by the method of the present invention has excellent monodispersity, and the particle size distribution index (PDI) of the colloidal silica prepared by the present invention is ≤0.1, thereby avoiding scratch defects caused by uneven particle size during polishing.
[0019] The present invention forms a chain-like branched protrusion structure through amino-carboxyl directional condensation and silane gradient coating, thereby preparing colloidal silica with a rough surface. The polishing liquid containing the colloidal silica of the present invention has a higher grinding rate in the chemical mechanical polishing of semiconductor devices, thereby improving the polishing efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figures 1 to 7 They are SEM images of colloidal silicon dioxide prepared in Examples 1-7 respectively; Figure 8 This is the SEM image of the colloidal silica in Comparative Example 1.
[0021] Figures 9 to 12 This is the SEM image of the colloidal silica prepared in Comparative Examples 2-5. DETAILED DESCRIPTION
[0022] Hereinafter, specific embodiments of the present invention will be described in detail, but the present invention is not limited to the embodiments including the following examples, and various modifications can be made within the scope that can achieve the purpose of the invention and does not exceed the gist of the invention.
[0023] The method for preparing high-purity monodisperse spherical colloidal silica for CMP of the present invention comprises the following steps: (a) Using siloxane as a raw material, adding a charge regulator aminopropylsilane and an alcohol solvent and mixing and stirring to form a mixed solution A; (b) mixing an alcohol solvent, an alkaline amino acid, ultrapure water and an alkaline substance to prepare a mixed solution B; (c) mixing the solution A and the solution B to react to prepare a silica sol; (d) distilling the silica sol under reduced pressure, and adding water to replace and remove the alcohol therein, thereby obtaining a colloidal silica with a rough surface.
[0024] In the present invention, steps (a) and (b) are not sequentially performed and can be prepared sequentially or simultaneously. In step (a) of the present invention, the siloxane is any one or a combination of tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, mercaptopropyltrimethoxysilane, epoxytrimethoxysilane, and mercaptopropyltriethoxysilane; The charge regulator is selected from aminopropyltrimethoxysilane, aminopropyltriethoxysilane or a combination thereof; In the present invention, siloxane can be hydrolyzed and condensed to form silicon dioxide nanoparticles, and the charge regulator is hydrolyzed and grown on the surface of the nanoparticles at the same time, connecting the amino functional groups on the surface of the nanoparticles to form sites for condensation of basic amino acids.
[0025] In step (a) of the present invention, the total metal ion impurities in the siloxane are ≤1ppm, and the metal ion impurities include sodium, potassium, calcium, magnesium, iron, nickel, etc.; the total anions in the siloxane are ≤1ppm, and the anions include chloride ions, etc.
[0026] In step (a) of the present invention, the content of the charge regulator is 1-10 wt %, preferably 2-5 wt % of the mixed solution A; the content of the alcohol solvent is 1-50 wt %, preferably 20-30 wt % of the mixed solution A; the remainder is siloxane. The contents in the present invention are all mass contents.
[0027] In step (b) of the present invention, the basic amino acid is selected from at least one of lysine, arginine, histidine, ornithine and citrulline, preferably lysine, arginine or a combination thereof; In step (b) of the present invention, the concentration of the basic amino acid in solution B is 0.1-3 wt %, preferably 0.5-1 wt %.
[0028] Basic amino acids can act as a catalyst in the preparation process, promote the hydrolysis of silane, and will not introduce metal ion impurities. Basic amino acids generally refer to amino acids with an isoelectric point greater than 7, which can react with charge regulators under alkaline conditions to form chain-like branched structures. Therefore, the concentration of amino acids needs to be controlled within a certain range. When the concentration of amino acids is too low, the amino acids are not grafted enough to form effective surface protrusions, and the surface tends to be smooth. As the concentration of amino acids increases, there are more chain-like branched structures and the surface is rougher. However, when the concentration of amino acids is too high, the hydrolysis of silane will be faster, the growth and nucleation of silane will be faster, and adhesion between particles will be easily formed, resulting in an increase in PDI and a deterioration in the monodispersity of silica.
[0029] Alkaline substances such as ammonia, triethoxypropylamine, and tetramethylammonium hydroxide do not contain metal ions and meet the semiconductor-grade purity requirements; at the same time, the volatility / decomposability of alkaline substances such as ammonia ensures that the residual alkali in the final product is ≤0.01wt%; In the present invention, the alcohol solvent can be selected from at least one of methanol, ethanol, isopropanol, butanol, isopentanol, ethylene glycol, propylene glycol, etc., preferably one or a combination of methanol, ethanol, isopropanol, more preferably methanol or ethanol.
[0030] In step (b) of the present invention, the concentration of the alcohol solvent in solution B is 60-90wt%, preferably 70-80wt%; In step (b) of the present invention, the concentration of the alkaline substance in solution B is 0.1-10 wt %, preferably 0.5-5 wt %.
[0031] In step (b) of the present invention, the alkaline substance may be one or more of ammonia water, triethoxypropylamine, tetramethylammonium hydroxide, etc., preferably ammonia water. The present invention has found through research that the concentration of ammonia water as a catalyst has a great influence on the surface roughness of the prepared colloidal silica. When the concentration of ammonia water is too high, it may cause the amino acid to be unable to effectively participate in the condensation reaction, reduce the condensation activity of the basic amino acid with the amino functional group on the charge regulator, thereby reducing the formation of side chains and making the surface smooth. On the other hand, when the concentration of ammonia water is too low, the hydrolysis rate of siloxane (such as tetramethoxysilane) slows down, resulting in incomplete reaction and prolonged reaction cycle. Too low ammonia concentration may cause the amino acid to lose the condensation activity with the amino functional group in the charge regulator, and also affect the hydrolysis of siloxane.
[0032] In step (c) of the present invention, the mass ratio of the mixed solution A to the solution B is 1:1-20, preferably 1:2-10.
[0033] In step (c) of the present invention, the reaction temperature of the mixed solution A and solution B is 30-40°C, preferably 33-37°C.
[0034] In step (c) of the present invention, the reaction time of the mixed solution A and solution B is 1-8 hours, preferably 1-2 hours.
[0035] In step (d) of the present invention, the temperature range of the reduced pressure distillation is preferably 40-80°C.
[0036] In step (d) of the present invention, the reduced pressure distillation needs to be concentrated to a desired solid content, preferably 10-40wt%, to obtain a high-purity silica sol product.
[0037] Specifically, the preparation method of high-purity monodisperse spherical colloidal silica for CMP of the present invention is as follows: (a) using electronic grade tetramethoxysilane or tetraethoxysilane as a raw material, adding a charge regulator aminopropyl trimethoxysilane or aminopropyl triethoxysilane and an alcohol solvent, mixing and stirring to form a mixed solution A, wherein the charge regulator content is 2-5 wt % of the mixed solution A; the alcohol solvent content is 20-30 wt % of the mixed solution A, and the rest is tetramethoxysilane or tetraethoxysilane; (b) mixing an alcohol solvent, arginine or lysine, ultrapure water and aqueous ammonia to prepare a mixed solution B, wherein the concentration of aqueous ammonia in solution B is 0.1-10 wt %; the concentration of the amino acid in solution B is 0.5-1 wt %, the content of the alcohol solvent is 70-80 wt % of the mixed solution A, and the balance is ultrapure water; (c) mixing solution A and solution B in a ratio of 1:2-10, reacting at 33-37° C. for 1-2 hours to prepare silica sol; (d) The silica sol is concentrated by vacuum distillation at 40-80°C to a solid content of 10-40wt%, and then constant liquid position replacement is performed at normal pressure. When the liquid temperature and the tower top temperature reach 100°C, the replacement is completed, and a high-purity monodisperse silica sol with a rough surface can be obtained.
[0038] The silica sol product prepared by the present invention has a significant difference in morphology compared with the existing high-purity CMP abrasive. In the present invention, the solvent, catalyst, etc. used can be removed during the distillation process, and no metal ion impurities are introduced. The metal ion impurities of the prepared colloidal silica are less than 1ppm, and the anion impurities are ≤1ppm.
[0039] In the present embodiment, in order to evaluate the grinding rate of the prepared colloidal silica as an abrasive, the colloidal silica was prepared into a polishing liquid composition for testing. The preparation method of the polishing liquid composition is as follows: colloidal silica abrasive: 15%, dispersant (ammonium polyacrylate, Mw=2000-5000): 0.5%, pH adjuster: adjusted to pH=10, and the rest is water.
[0040] Preparation steps: Add colloidal silica abrasive and deionized water into a stirrer and stir, then add ammonium polyacrylate (Mw=2000-5000) and the like, continue stirring, add 0.1M nitric acid at room temperature to pH=10.0±0.2, and continue stirring for 30 minutes; filter through a 0.1μm nylon filter element to remove agglomerated particles to obtain the final polishing liquid. Example
[0041] In the following examples, unless otherwise specified, the raw materials, reagents or processing techniques used are all commercially available raw materials or conventional processing techniques commonly used in the art.
[0042] The raw materials used in the embodiments of the present invention are as follows: Tetramethoxysilane (electronic grade) Tetraethoxysilane (electronic grade) Methanol (analytical grade) Ethanol (analytical grade) Lysine (analytical grade) Arginine (analytical grade) Ammonia (analytical grade) Aminopropyltrimethoxysilane (electronic grade) Aminopropyltriethoxysilane (electronic grade) <Test Method> Dynamic light scattering particle size (DLS size) and PDI of colloidal silica: measured using a Malvern laser particle size analyzer; Metal ion impurities: measured by inductively coupled plasma mass spectrometry (ICP-MS); Morphology photo of colloidal silica: taken using a scanning electron microscope.
[0043] Polishing rate test: An 8-inch silicon wafer (with a thermally oxidized SiO2 layer on the surface, with an initial thickness of 1000±10nm) was polished using an IC1010 porous polyurethane pad on a CMP polisher: down pressure: 2.0 psi, polishing head speed: 100 rpm, polishing disc speed: 80 rpm, polishing liquid flow rate: 150 mL / min. An ellipsometer (nano spec Ⅱ) was used to measure the thickness of the film before and after polishing, and the data was recorded to measure the film thickness before and after the polishing time was 10 minutes (Δh, unit: angstrom); the final polishing rate (RR) = Δh / polishing time (angstrom / min). Example 1
[0044] Methanol and aminopropyltrimethoxysilane were added to electronic grade tetramethoxysilane. After stirring evenly, a mixed solution A was obtained. The methanol content in mixed solution A was 30wt%, the aminopropyltrimethoxysilane content was 5wt%, and the rest was tetramethoxysilane; ammonia water, ultrapure water, lysine, and methanol were configured to form a mixed solution B. The ammonia concentration in the configured mixed solution B was 0.5wt%, the methanol content was 70 wt%, the concentration of lysine in mixed solution B was 0.5wt%, and the rest was ultrapure water. Mixed solution A and mixed solution B were reacted at 33℃ for 2h in a mass ratio of 1:10 to generate silica sol. The silica sol was concentrated to 40wt% by vacuum distillation at 75℃, and then constant liquid position replacement was performed at normal pressure. When the liquid temperature and the tower top temperature reached 100℃, the replacement was completed, and a high-purity monodisperse silica sol with rough surface was obtained. The particle size was 69nm and the PDI was 0.041 measured by Malvern laser particle size analyzer. Example 2
[0045] (1) Methanol and aminopropyltrimethoxysilane are added to electronic grade tetramethoxysilane, and the mixture is stirred to obtain a mixed solution A. The content of methanol in the mixed solution A is 20 wt %, the content of aminopropyltrimethoxysilane is 2 wt %, and the rest is tetramethoxysilane.
[0046] (2) Ammonia water, ultrapure water, lysine, and methanol are prepared into a mixed solution B. The prepared mixed solution B has an ammonia concentration of 2 wt %, a methanol content of 80 wt %, a lysine concentration of 1 wt %, and the balance is ultrapure water.
[0047] (3) Mixed solution A and mixed solution B were reacted at a mass ratio of 1:10 at 37°C for 1 hour to generate silica sol.
[0048] (4) The silica sol is concentrated to 10 wt% by vacuum distillation at 40°C, and then constant liquid position replacement is performed at normal pressure. When the liquid temperature and the tower top temperature reach 100°C, the replacement is completed, and a high-purity monodisperse silica sol with a rough surface is obtained. The particle size is 50 nm and the PDI is 0.046 as measured by a Malvern laser particle size analyzer. Example 3
[0049] (1) Add ethanol and aminopropyltriethoxysilane to electronic grade tetraethoxysilane, and stir to obtain a mixed solution A. The mixed solution A contains 25 wt % ethanol, 3 wt % aminopropyltriethoxysilane, and the rest is tetraethoxysilane.
[0050] (2) Ammonia water, ultrapure water, arginine, and ethanol are prepared into a mixed solution B. The prepared mixed solution B has an ammonia concentration of 2 wt %, an ethanol content of 75 wt %, an arginine concentration of 0.7 wt %, and the balance is ultrapure water.
[0051] (3) Mixed solution A and mixed solution B were reacted at a mass ratio of 1:10 at 37°C for 1 h to generate silica sol.
[0052] (4) The silica sol is concentrated to 10 wt% by vacuum distillation at 40°C, and then constant liquid position replacement is performed at normal pressure. When the liquid temperature and the tower top temperature reach 100°C, the replacement is completed, and a high-purity monodisperse silica sol with a rough surface is obtained. The particle size is 73 nm and the PDI is 0.073 as measured by a Malvern laser particle size analyzer. Example 4
[0053] (1) Methanol and aminopropyltrimethoxysilane are added to electronic grade tetramethoxysilane, and the mixture is stirred to obtain a mixed solution A. The content of methanol in the mixed solution A is 30 wt%, the content of aminopropyltrimethoxysilane is 4 wt%, and the rest is tetramethoxysilane.
[0054] (2) Ammonia water, ultrapure water, lysine, and methanol are prepared into a mixed solution B. The prepared mixed solution B has an ammonia concentration of 5 wt %, a methanol content of 70 wt %, a lysine concentration of 0.5 wt %, and the balance is ultrapure water.
[0055] (3) Mixed solution A and mixed solution B were reacted at a mass ratio of 1:6 at 33° C. for 2 h to generate silica sol.
[0056] (4) The silica sol is concentrated to 40 wt% by vacuum distillation at 80°C, and then constant liquid position replacement is performed at normal pressure. When the liquid temperature and the tower top temperature reach 100°C, the replacement is completed, and a high-purity monodisperse silica sol with a rough surface is obtained. The particle size is 63 nm and the PDI is 0.052 as measured by a Malvern laser particle size analyzer. Example 5
[0057] (1) Methanol and aminopropyltrimethoxysilane are added to electronic grade tetramethoxysilane, and the mixture is stirred to obtain a mixed solution A. The content of methanol in the mixed solution A is 30 wt %, the content of aminopropyltrimethoxysilane is 5 wt %, and the rest is tetramethoxysilane.
[0058] (2) Ammonia water, ultrapure water, lysine, and methanol are prepared into a mixed solution B. The prepared mixed solution B has an ammonia concentration of 10 wt %, a methanol content of 70 wt %, a lysine concentration of 0.1 wt %, and the balance is ultrapure water.
[0059] (3) Mixed solution A and mixed solution B were reacted at a mass ratio of 1:5 at 33° C. for 1 h to generate silica sol.
[0060] (4) The silica sol is concentrated to 40 wt% by vacuum distillation at 75°C, and then constant liquid position replacement is performed at normal pressure. When the liquid temperature and the tower top temperature reach 100°C, the replacement is completed, and a high-purity monodisperse silica sol with a rough surface is obtained. The particle size is 71 nm and the PDI is 0.074 as measured by a Malvern laser particle size analyzer. Example 6
[0061] (1) Methanol and aminopropyltrimethoxysilane are added to electronic grade tetramethoxysilane, and the mixture is stirred to obtain a mixed solution A. The content of methanol in the mixed solution A is 20 wt %, the content of aminopropyltrimethoxysilane is 1 wt %, and the rest is tetramethoxysilane.
[0062] (2) Ammonia water, ultrapure water, lysine, and methanol are prepared into a mixed solution B. The prepared mixed solution B has an ammonia concentration of 0.1 wt %, a methanol content of 70 wt %, a lysine concentration of 3 wt %, and the balance is ultrapure water.
[0063] (3) Mixed solution A and mixed solution B were reacted at a mass ratio of 1:2 at 33° C. for 1 h to generate silica sol.
[0064] (4) The silica sol is concentrated to 20 wt% by vacuum distillation at 75°C, and then constant liquid position replacement is performed at normal pressure. When the liquid temperature and the tower top temperature reach 100°C, the replacement is completed, and a high-purity monodisperse silica sol with a rough surface is obtained. The particle size is 67 nm and the PDI is 0.081 as measured by a Malvern laser particle size analyzer. Example 7
[0065] The preparation method is the same as that in Example 1, except that the concentration of lysine in the mixed solution B is 5 wt %. The silica sol with a rough surface is obtained in the preparation method, and the particle size is 94 nm and the PDI is 0.21 as measured by a Malvern laser particle size analyzer.
[0066] Comparative Example 1 PL-3 silica sol produced by Japan Fuso Company, morphology photos are attached Figure 8 , a significant peanut-shaped fusion particle structure can be seen, and the surface is relatively smooth.
[0067] Comparative Example 2 The preparation method is the same as that of Example 1, except that the concentration of aqueous ammonia in the prepared mixed solution B is 15 wt %. The surface of the colloidal silicon dioxide obtained in this preparation method is relatively smooth.
[0068] Comparative Example 3 The preparation method is the same as that of Example 1, except that the concentration of aqueous ammonia in the prepared mixed solution B is 0.05 wt %. The surface of the colloidal silicon dioxide obtained in this preparation method is relatively smooth.
[0069] Comparative Example 4 The preparation method is the same as that of Example 1, except that no amino acid is added during the preparation process. The surface of the colloidal silicon dioxide obtained in this preparation method is relatively smooth.
[0070] Comparative Example 5 The preparation method is the same as that of Example 1, except that the concentration of lysine in the mixed solution B is 0.07 wt %. The surface of the colloidal silicon dioxide obtained in the preparation method is relatively smooth.
[0071] Application Examples Preparation of polishing liquid: Raw material composition (by mass percentage): colloidal silica abrasive prepared in Examples 1-8 of the present invention or Comparative Examples 1-4: 15%, dispersant (ammonium polyacrylate, Mw=2000-5000): 0.5%, pH adjuster: adjusted to pH=10, and the rest is water.
[0072] Preparation steps: Add colloidal silica abrasive and deionized water into a stirrer and stir, then add ammonium polyacrylate, etc., continue stirring, the temperature is ≤25°C; add 0.1M nitric acid until pH=10.0±0.2, continue stirring for 30 minutes; filter through a 0.1μm nylon filter to remove agglomerated particles, obtain the final polishing liquid, and test the grinding rate Table 1 Colloidal silica ion content and polishing rate of polishing liquid prepared therefrom in Examples and Comparative Examples
[0073] See the instruction manual Figure 1-12 The preparation method of the embodiment of the present invention can obtain colloidal silica with a rough surface, which has a significant improvement in grinding rate compared with commercially available smooth colloidal silica, thereby further improving the polishing efficiency. The colloidal silica obtained in the embodiment of the present invention not only has a rough surface, but also has the advantages of monodispersity and high purity, which can meet the purity requirements in the field of semiconductor polishing and is conducive to reducing polishing defects.
[0074] It can be seen from Example 1 and Comparative Example 4 that the addition of amino acids plays a major role in regulating the morphology of colloidal silica. In Comparative Example 4, no amino acids are added, and a rough spherical structure with surface protrusions cannot be formed. Therefore, it can be inferred that amino acids are the key to forming colloidal silica with a rough surface. It may be that the basic amino acids condense with the amino groups on the surface of the nanoparticles, continue to condense with the amino acids to form a chain branched structure to form protrusions, and at the same time, the silane continues to hydrolyze and condense to grow, thereby finally forming nanoparticles with a rough surface.
[0075] In Examples 2 and 3, the concentration of ammonia water was not changed, and the parameters such as alcohol content, amino acid, temperature, charge regulator, and siloxane were changed within a certain range. It was found that the surface roughness of the colloidal silica obtained in Examples 2 and 3 was not much different (see Appendix). Figure 2 and attached Figure 3 ), and there is no significant change in the grinding rate. Through the test data of Examples 1-7 of the present invention and Comparative Examples 2-3, it can be found that the concentration of ammonia water as a catalyst will have a greater impact on the surface roughness of the prepared colloidal silica, and it is beneficial to obtain colloidal silica with a rough surface within a certain concentration range. When the concentration of ammonia water is too high, it may cause the amino acid to be unable to effectively participate in the condensation reaction, reduce the condensation activity of the basic amino acid with the amino functional group on the charge regulator, thereby reducing the formation of side chains and making the surface smooth. When the concentration of ammonia water is too low, the hydrolysis rate of siloxane (such as tetramethoxysilane) slows down, resulting in incomplete reaction and a longer reaction cycle. Too low ammonia concentration may cause the amino acid to lose the condensation activity with the amino functional group in the charge regulator, and also affect the hydrolysis of siloxane to form colloidal silica with a smooth surface.
[0076] The concentration of amino acids also affects the surface roughness to a certain extent. Comparative Example 5 shows that when the amino acid concentration is too low, chain-like protrusions cannot be grafted on the surface, and thus, rough-surfaced silica cannot be formed. However, Example 7 shows that when the amino acid concentration is too high, the amino acid accelerates the hydrolysis of catalytic silane, accelerates nucleation and growth, and causes the monodispersity of the particles to deteriorate, with PDI>0.1.
Claims
1. A method for preparing colloidal silicon dioxide with a rough surface, characterized in that: The steps include: (a) Siloxane is used as a raw material, and a charge regulator aminopropylsilane and an alcohol solvent are added and mixed and stirred to form a mixed solution A; (b) The alcohol solvent, alkaline amino acid, ultrapure water and alkaline substance are mixed to prepare a mixed solution B, wherein the alkaline substance includes one or more combinations of ammonia water, tetramethylammonium hydroxide and triethoxypropylamine, and the alkaline amino acid is selected from one or more combinations of lysine, arginine, histidine, ornithine and citrulline, and the concentration of the alkaline amino acid in the solution B is 0.1-3wt%, and the concentration of the alkaline substance in the solution B is 0.1-10wt%; (c) The solution A and the solution B are mixed and reacted to prepare a silica sol; (d) The silica sol is subjected to reduced pressure distillation, and water is added to replace and remove the alcohol therein to obtain a colloidal silica with a rough surface.
2. The method according to claim 1, characterized in that: The concentration of the basic amino acid in the solution B is 0.5-1 wt %.
3. The method according to claim 1, characterized in that: The concentration of the alkaline substance in the solution B is 0.5-5 wt %.
4. The method according to claim 1, characterized in that: The basic amino acid is selected from at least one of lysine and arginine.
5. The method according to any one of claims 1 to 4, characterized in that: The siloxane is selected from one or more combinations of tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, mercaptopropyltrimethoxysilane, epoxytrimethoxysilane, and mercaptopropyltriethoxysilane; the charge regulator is selected from one or more combinations of aminopropyltrimethoxysilane and aminopropyltriethoxysilane; the alcohol solvent is selected from one or more combinations of methanol, ethanol, isopropanol, butanol, isopentanol, ethylene glycol, and propylene glycol.
6. The method according to any one of claims 1 to 4, characterized in that: In step (a), the content of the charge regulator is 1-10 wt % of solution A; the content of the alcohol solvent in step (a) is 1-50 wt % of solution A; and the content of the alcohol solvent in step (b) is 60-90 wt % of solution B.
7. The method according to any one of claims 1 to 4, characterized in that: The mass ratio of solution A to solution B is 1:1-20; the reaction temperature of solution A and solution B is 30-40°C; the reaction time of solution A and solution B is 1-8h; the temperature range of the reduced pressure distillation is 40-80°C, and the reduced pressure distillation is concentrated to a solid content of 10-40wt%.
8. A colloidal silica having a rough surface, characterized in that: The colloidal silicon dioxide is prepared according to the method for preparing colloidal silicon dioxide according to any one of claims 1 to 7.
9. A CMP polishing composition, characterized in that: The invention comprises the colloidal silica abrasive according to claim 8.
10. Use of the colloidal silica according to claim 8 as an abrasive in CMP mechanical polishing.
Citation Information
Patent Citations
Method for preparing aluminum nitride fibers through carbothermal reduction
CN112142020A
Semiconductor Device
US20180035512A1
Method for producing cationically modified silica and cationically modified silica dispersion
CN109071238A
Method for preparing self-roughening surface by polarity induced phase separation method and product thereof
CN114874697A
Aqueous dispersions comprising inorganic particles
CN117693563A